Медіакультура як унікальний соціальний інститут інформаційної епохи - Пилюк, Л. О. (ХНУРЕ, 2021)
Modern society is characterized by the transformation of information into global resource of mankind, the creation of new information technologies, transformation of mass media into mass communication, globalization of the world information space. The paper considers prospects for the development of media culture of the individual, it is emphasized that the media culture is a unique social institution of the information age
Keywords: філософія; медіакультура